Approximation of Solutions of an Equilibrium Problem in a Banach Space - Hecai Yuan; Guohong Shi (Journal of Applied Mathematics)
An equilibrium problem is investigated based on a hybrid projection iterative algorithm. Strong convergence theorems for solutions of the equilibrium problem are established in a strictly convex and uniformly smooth Banach space which also enjoys the Kadec-Klee property.